Seismic Performance Evaluation of Laboratory Building with Concrete Column Jacketing Based on ASCE 41-17 using Pushover Analysis - Aditya Rihadatul Aisy; Josia Irwan Rastandi; Jessica Sjah (G-Tech: Jurnal Teknologi Terapan, 2026)
This study presents comprehensive seismic performance evaluation on the laboratory building structure designed using the old regulations (SNI 1726:2002 and SNI 2847:2002) and has been strengthened with concrete column jacketing through a pushover analysis procedure based on ASCE 41-17 guidelines. Based on the global performance of the structure, the structure drift have met the performance targets with a maximum drift of 1.92% for the X direction and 1.96% for the Y direction. Based on the analysis of the deformation-controlled action, the rotation values ​​that occur in the beam components have met the performance targets with a maximum rotation of 0.0066 for negative moments and 0.0073 for positive moments. While the strain that occurs in the column components have also met the performance targets with a maximum strain of 0.0032 for rebar compression strain, 0.0131 for rebar tensile strain, and 0.0024 for concrete compression strain. Then, based on the analysis of the force-controlled action, the DCR values ​​for shear and axial in the column components have met the performance targets with a maximum value for shear of 0.89 and for axial of 0.61. While the DCR values ​​for shear in the beam components partially exceed the performance targets with a maximum value of 1.29.